2016
DOI: 10.15408/jch.v4i2.3599
|View full text |Cite
|
Sign up to set email alerts
|

Menjejaki Akses Terhadap Keadilan Dalam Konflik Agraria: Studi Pada Warga Moro-Moro Register 45 Mesuji Lampung

Abstract: Agrarian conflictare inextricably linked to issues of injustice. There is a view that in equality in the agrarian conflicts can and should be resolved through legal measures, which were touted asthe establishmentand enforcement measures. By elaborating the idea of ​​access to justice within the framework of ROLAX and ROLGOM, as well as approach esthatare reviewed by the Theory access Ribot and Peluso, this paper seeks to study how access to justice can be achieve din agrarian conflicts. Of elaboration that acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Banjar Margo case is an example of prolonged and unsolved agrarian conflict in Indonesia involving peasant versus plantation companies. Moreover, the prolonged conflict could lead to humanitarian crises where the rights of the people are abandoned while violence then tend to be cyclical, as exemplified in the Register 45 of Mesuji District [6], [7], next to the Banjar Margo district. The central government has prioritized the Agrarian Policy; however, data collected by Konsorsium Pembaruan Agraria (KPA) showed that agrarian conflict tends to increase under the Joko Widodo presidency, consisting of 1770 cases in their first period (2014-2019) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The Banjar Margo case is an example of prolonged and unsolved agrarian conflict in Indonesia involving peasant versus plantation companies. Moreover, the prolonged conflict could lead to humanitarian crises where the rights of the people are abandoned while violence then tend to be cyclical, as exemplified in the Register 45 of Mesuji District [6], [7], next to the Banjar Margo district. The central government has prioritized the Agrarian Policy; however, data collected by Konsorsium Pembaruan Agraria (KPA) showed that agrarian conflict tends to increase under the Joko Widodo presidency, consisting of 1770 cases in their first period (2014-2019) [8].…”
Section: Introductionmentioning
confidence: 99%